2022
DOI: 10.3390/cells11121939
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Cortical Excitability in a Conditional Model of PCDH19 Disorder

Abstract: PCDH19 epilepsy (DEE9) is an X-linked syndrome associated with cognitive and behavioral disturbances. Since heterozygous females are affected, while mutant males are spared, it is likely that DEE9 pathogenesis is related to disturbed cell-to-cell communication associated with mosaicism. However, the effects of mosaic PCDH19 expression on cortical networks are unknown. We mimicked the pathology of DEE9 by introducing a patch of mosaic protein expression in one hemisphere of the cortex of conditional PCDH19 knoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…disturbance and diseases such as epilepsy and neurodevelopmental disorders (Bhat et al, 2014;Lamers et al, 2022;Medina et al, 2022). Close et al (2012) showed that deleting Satb1 from all MGE-derived interneurons at an early developmental stage (using the Dlx5/6 Cre driver line), and thus causing a reduction of their number, led to electrographic interictal discharges during slow-wave sleep (SWS).…”
Section: Context Dependent Involvement Role Of Sst-expressing Interne...mentioning
confidence: 99%
“…disturbance and diseases such as epilepsy and neurodevelopmental disorders (Bhat et al, 2014;Lamers et al, 2022;Medina et al, 2022). Close et al (2012) showed that deleting Satb1 from all MGE-derived interneurons at an early developmental stage (using the Dlx5/6 Cre driver line), and thus causing a reduction of their number, led to electrographic interictal discharges during slow-wave sleep (SWS).…”
Section: Context Dependent Involvement Role Of Sst-expressing Interne...mentioning
confidence: 99%
“…Animal studies have indicated that active measures of EEG recordings track cortical excitability in mice [8] add Wei's study if published soon. Perturbing the brain in living humans often involves invasive intracranial surgeries [5; 20; 21; 22; 23], or expensive equipment only accessible to a minority of patient groups such as transcranial magnetic stimulation (TMS), though the perturbation is diffuse and spatially non-specific [6; 7; 24].…”
Section: Introductionmentioning
confidence: 99%
“…However, delivering perturbations to the brain is generally invasive in practice, requiring implantation of intracranial electrodes or other invasive devices. Animal studies in mice have successfully used electrical stimulation as a perturbation to track cortical excitability [14]. In humans, perturbation studies have used a subset of patients with focal epilepsy eligible for resection surgeries who are undergoing monitoring to confirm the seizure onset zone, where electrodes are placed strategically for that patient’s unique seizure onset zone [15; 16; 17; 18; 19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental abnormalities involving the limbic structures, particularly the parahippocampal and entorhinal gyri, likely represent a measurable anatomic consequence of the altered expression of the PCDH19 protein on cortical folding and white matter organization in these anatomic areas [12], and are functionally re ected in the phenotypic features involving neuropsychiatric symptoms, cognitive and communicative skills and local epileptogenesis [3]. Recent studies on animal models have contributed to clarify how PCDH19 mutations alter brain network formation and maintenance [13], and have identi ed mechanisms by which focal mosaic mutations disrupt cortical networks [14] and impair neuronal activity and connectivity [15].…”
Section: Introductionmentioning
confidence: 99%